2013
DOI: 10.35790/eg.1.1.2013.1923
|View full text |Cite
|
Sign up to set email alerts
|

Status Kebersihan Mulut Dan Status Karies Gigi Mahasiswa Pengguna Alat Ortodontik Cekat

Abstract: Fixed orthodontic appliance are now widely used in society, but people often do not realize the risks of using this appliance such as oral hygiene and caries problem. The design of this appliance is more difficult to clean than removable orthodontic appliance, so that patient is more difficult to maintain oral hygiene. Poor oral hygiene can also cause caries. The purpose of this study is to obtain a description of the oral hygiene status and caries status of dental student using fixed orthodontic appliance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 4 publications
0
3
0
13
Order By: Relevance
“…Fixed orthodontic toothbrush care currently has been used by many. Infants and Adults have to utilize fixed orthodontic toothbrush not only for dental care but instead, and it is part of the lifestyle [1]. Based on previous research, the result showed that most of adult orthodontic patient did the treatment for appearance aspect [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixed orthodontic toothbrush care currently has been used by many. Infants and Adults have to utilize fixed orthodontic toothbrush not only for dental care but instead, and it is part of the lifestyle [1]. Based on previous research, the result showed that most of adult orthodontic patient did the treatment for appearance aspect [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the general application the public does not realize like oral hygiene in the use of removable orthodontic. Use of removable orthodontic is also impacted effects on oral hygiene changing and flora composition on the oral cavity [1]. Oral hygiene is proclaimed to be the essential part that can affect plaque accumulation that usually happens in around bracket [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ini juga bisa meningkat pengetahuan siswa tentang perawatan gigi dan Perubahan warna gigi, terutama saat menjalani perawatan ortodonti. [37], [38]…”
Section: Pendahuluanunclassified
“…5,6 Pengendalian plak yang teratur diperlukan untuk menjaga kebersihan mulut selama perawatan ortodonti cekat. 7 Pengendalian plak dapat dilakukan secara mekanis dan kimiawi. Sikat gigi merupakan alat utama dalam melaksanakan pengendalian plak secara mekanis.…”
Section: Pendahuluanunclassified